The consequences of the global financial crisis : the rhetoric of reform and regulation - Grant, Wyn.; Wilson, Graham K. (Oxford : Oxford University Press, 2012)
Systematically exploring the consequences of the global financial crisis, this text focuses primarily on the impact on policy and politics. It asks how governments responded to the challenges that the crisis has posed, and the policy and political impact of the combination of both the crisis itself and these responses.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on July 12, 2012).
Keywords: Global Financial Crisis, 2008-2009.; Financial institutions -- Government policy; International finance -- Law and legislation